Mr-factors and Qr-factors for near quasinorm on certain sequence spaces - Piyapong Niamsup; Yongwimon Lenbury (International Journal of Mathematics and Mathematical Sciences)
We study the multiplicativity factor and quadraticity factor for near quasinorm on certain sequence spaces of Maddox, namely, l(p) and l∞(p), where p=(pk) is a bounded sequence of positive real numbers.